2020
DOI: 10.1186/s13045-020-00907-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer history is an independent risk factor for mortality in hospitalized COVID-19 patients: a propensity score-matched analysis

Abstract: Background: Although research on the effects of comorbidities on coronavirus disease 2019 (COVID-19) patients is increasing, the risk of cancer history has not been evaluated for the mortality of patients with COVID-19. Methods: In this retrospective study, we included 3232 patients with pathogen-confirmed COVID-19 who were hospitalized between January 18th and March 27th, 2020, at Tongji Hospital in Wuhan, China. Propensity score matching was used to minimize selection bias. Results: In total, 2665 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
193
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(219 citation statements)
references
References 42 publications
14
193
3
3
Order By: Relevance
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
“…The repetition of patients from the same hospital was examined during the same period. Most of the selected studies (29/52) were performed in China 6,17‐25,27‐32,35‐37,50,59‐67 . Ten studies were performed in multicenters 6,17,23,34,45,49,57,58,60,64 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First reports from China indicated that cancer patients with Covid-19 may have a higher risk of a severe disease course and less favorable outcome compared to noncancer patients with Covid-19. [11][12][13][14] However, sample sizes were small and patient cohorts consisted mainly of patients with solid tumors. 11,12 Recently, two reports from China and one from the UK described larger multi-center studies on cancer patients with Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, dyspnea, hemoptysis, and unconsciousness were clinical predictors of critical illness [ 23 ]. While several clinical predictors for severe COVID-19 (dyspnea [ 24 ], old age [ 25 ], type II diabetes [ 26 ], obesity [ 27 ], possibly hypertension [ 28 ], history of cancer [ 29 ], cardiovascular disease [ 30 ], or increased ratios of CD4/CD8 [ 31 ], neutrophils/lymphocytes [ 32 ], and CRP/lymphocytes [ 33 ]) have been identified, no study has assessed clinical predictors for SARS-CoV-2 positivity. This knowledge is important for the upcoming phase, when the ratio of patients affected to patients tested will remain low in most test centers.…”
Section: Discussionmentioning
confidence: 99%